Psychological Wellbeing, Mindfulness, and Immunity of Teachers in Second or Foreign Language Education: A Theoretical Review - Li, Shengji (Frontiers in Psychology, 2021)
The emotions and affective factors of teachers play quintessential roles in academic contexts as they influence almost all aspects of their profession. T provide a theoretical review of some psychology constructs of teachers in this area, this study examines the psychological wellbeing, mindfulness, and immunity of teachers as three novel variables. More specifically, this study presents the definitions, dimensions, theories, and frameworks related to this domain drawing on positive psychology, complexity/dynamic systems theory, self-organization process, reflexive self-consciousness theory, integrative awareness theories, and mindfulness framework. These theoretical underpinnings explain the constructs and the way they function in second language education. Then, to provide evidence and justify the findings and propositions, empirical studies on each of the variables are reviewed. Finally, implications, research gaps, and suggestions for future inquiries are offered to interested researchers.